2004
DOI: 10.1110/ps.04731004
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical characterization of the free IκBα ankyrin repeat domain in solution

Abstract: The crystal structure of IB␣ in complex with the transcription factor, nuclear factor -B (NF-B) shows six ankyrin repeats, which are all ordered. Electron density was not observed for most of the residues within the PEST sequence, although it is required for high-affinity binding. To characterize the folded state of IB␣ (67-317) when it is not in complex with NF-B, we have carried out circular dichroism (CD) spectroscopy, 8-anilino-1-napthalenesulphonic acid (ANS) binding, differential scanning calorimetry, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
151
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(167 citation statements)
references
References 51 publications
14
151
0
2
Order By: Relevance
“…This type of conformational heterogeneity has been demonstrated elegantly for the six ankyrin repeats of IκBα. Hydrogen exchange studies show that ankyrin repeats 1, 5, and 6 are substantially disordered in the unbound state [59], but repeats 5 and 6 become structured on binding to NF-κB [60]. A similar disorder-order transition is seen crystallographically for the first repeat of the Notch ankyrin domain when binding the transcription factor CSL [51,61,62].…”
Section: Multistate Equilibrium Folding Of Repeat Proteinsmentioning
confidence: 73%
“…This type of conformational heterogeneity has been demonstrated elegantly for the six ankyrin repeats of IκBα. Hydrogen exchange studies show that ankyrin repeats 1, 5, and 6 are substantially disordered in the unbound state [59], but repeats 5 and 6 become structured on binding to NF-κB [60]. A similar disorder-order transition is seen crystallographically for the first repeat of the Notch ankyrin domain when binding the transcription factor CSL [51,61,62].…”
Section: Multistate Equilibrium Folding Of Repeat Proteinsmentioning
confidence: 73%
“…Exactly analogous to our results, they found that central repeats are more protected from exchange than are repeats at both ends. 35 Figure 4 also shows the Ising model predictions for the denaturant-dependence of the protection factors for each helix. Overall, the model captures the behavior of the different helices supporting the idea that each helix is an independent folding unit.…”
Section: Native State Hydrogen Exchange (Nhx)mentioning
confidence: 99%
“…1), I B␣ appears to be compactly folded (20,22). However, ARs 1, 5, and 6 in free I B␣ readily exchange most of their amide protons, indicating that they are highly solvent accessible and perhaps unfolded (35). Circular dichroism (CD) showed that all of the secondary structure was present in both free and NF-B-bound I B␣ (35).…”
mentioning
confidence: 99%
“…However, ARs 1, 5, and 6 in free I B␣ readily exchange most of their amide protons, indicating that they are highly solvent accessible and perhaps unfolded (35). Circular dichroism (CD) showed that all of the secondary structure was present in both free and NF-B-bound I B␣ (35). However, CD does not probe tertiary structure or protein flexibility, both of which are probed by amide H/ 2 H exchange.…”
mentioning
confidence: 99%
See 1 more Smart Citation